56.6k views
0 votes
Find f(4) when f(x)=4x^2 - 2 x - 4

User Pronngo
by
5.2k points

1 Answer

1 vote

Answer:

52

Explanation:


f(x)=4x^2-2x-4


f(4)=4(4)^2-2(4)-4 (I replaced
x with
(4) since we are to find
f(4).)


f(4)=4(16)-2(4)-4 (By the order of operations, we take care of the exponents before whatever else we have here.)


f(4)=64-8-4 (By the order of operations, we take care of the multiplication as we see if left to right.)


f(4)=56-4 (By the order of operations, we perform addition/subtraction as we see it left to right.)


f(4)=52 (This completes the simplification.)

We could have also put this in our calculator as:

4(4)^2 - 2(4) - 4

This would have returned 52.

User Vhs
by
4.8k points